(untitled) (Global Journal of Science Frontier Research, 2018)
The role of avifauna in the ecosystem are as scavenger, pollinators, seeds dispersal agents and predators of insect pest and also an important indicator to evaluate different habitats both qualitatively and quantitatively. Wetlands are also important for birds for their feeding, roosting, nesting and rearing young activities. The present study was conducted in the cultivated areas and water bodies of the villages adjacent to Kumbakonam. Birds were estimated using total count method. Activity pattern and physio-chemical parameters of fresh water habitats were identified using standard methodologies. Thirty one species of water birds belonging to 14 families have been identified in the waterways at the study area. The density of diving birds, swimming birds, small waders, large waders and aerial foragers were slightly higher in the month of November than March. Most of the birds observed and recorded higher in monsoon followed by pre-monsoon and post-monsoon seasons. Physio-chemical parameters of water in the study sites was slightly alkaline nature and contained high amounts of pH, dissolved oxygen, electrical conductivity, salinity and turbidity throughout the study period.